Multiple Two-Photon Targeted Whole-Cell Patch-Clamp Recordings From Monosynaptically Connected Neurons in vivo - Jouhanneau, Jean-Sébastien; Poulet, James F. A. (Frontiers in Synaptic Neuroscience, 2019)
Although we know a great deal about monosynaptic connectivity, transmission and integration in the mammalian nervous system from in vitro studies, very little is known in vivo. This is partly because it is technically difficult to evoke action potentials and simultaneously record small amplitude subthreshold responses in closely (< 150 µm) located pairs of neurons. To address this, we have developed in vivo two-photon targeted multiple (2 – 4) whole-cell patch clamp recordings of nearby neurons in superficial cortical layers 1 to 3. Here we describe a step-by-step guide to this approach in the anesthetised mouse primary somatosensory cortex, including: the design of the setup, surgery, preparation of pipettes, targeting and acquisition of multiple whole-cell recordings, as well as in vivo and post-hoc histology. The procedure takes ~ 4 hours from start of surgery to end of recording and allows examinations both into the electrophysiological features of unitary excitatory and inhibitory monosynaptic inputs during different brain states as well as the synaptic mechanisms of correlated neuronal activity.